Building a Digital Village to Improve Services and Independence of Village Communities After the Covid-19 Pandemic - Lutfi, Moch.; Nath, Gourab (LPPM Universitas Yudharta Pasuruan, 2023)
Bakalan Village is one of the villages initiated by the government of Pasuruan Regency to become a digital village. To build a digital-based village, it is necessary to have a system that can help and facilitate this work. One of the team's dedication efforts in realizing this digital village is to provide assistance fund training to the community and Bakalan village government employees regarding online marketplace management, service systems, and village administration systems. The purpose of this activity is to increase community knowledge and skills in managing online marketplaces, service systems, and village administration systems through an Android application. This service activity is carried out through the stages of planning, implementing, and evaluating activities. From this activity the service team develops and builds an Android-based mail service application, a village website application, and an online buying and selling system application as a media promotion Village-Owned Enterprise products.